Optical and photoacoustic investigation of AZO/Ag/AZO transparent conductive coating for solar cells. Issue 10 (7th September 2016) - Cesarini, Gianmario; Leahu, Grigore; Grilli, M. L.; Sytchkova, A.; Sibilia, Concita; Li Voti, Roberto
Abstract: Great attention has been recently paid to transparent conductive oxides (TCOs) due to their application in optoelectronic devices, flat panel displays, solar cells, and anti‐static coatings. Concerning photovoltaic applications, the reduction of the material and processing costs are the key factors in the production process. Due to In scarcity and cost, alternative solutions to indium tin oxide (ITO) are needed. Al‐doped ZnO (AZO) meets the requirements for application in thin film solar cells, thanks to its good optoelectrical properties, low cost and higher resistance to Hydrogen‐reach plasmas. Recently many papers analyze innovative AZO based TCO structures where a thin layer of Silver is introduced in the TCO so to increase the electrical conductivity without loosing transparency. In this work we study the transparency and the electrical sheet resistance of a multilayer AZO/Ag/AZO as a function of the silver thin layer, and discuss the problem of optimizing the thicknesses of the multilayers to get the best performances. We have realized an AZO/Ag/AZO multilayer coating by radio frequency (RF) sputtering with an optimal thickness of the silver layer. Optical and photoacoustic spectroscopy (PAS) have been applied to perform the characterization of the sample. In particular PAS seems the most efficient technique to test directly the absorbance of the structure which should be reduced to avoid overheating and loss of the solar cell efficiency. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)